2023
DOI: 10.2478/jvetres-2023-0044
|View full text |Cite
|
Sign up to set email alerts
|

Levels of caesium-137 in food of animal origin in Poland

Magdalena Gembal,
Paweł Czerski,
Ewelina Milczarczyk
et al.

Abstract: Introduction Radioactive contamination of the environment is one of the greatest threats after a nuclear accident due to released radionuclides. From a radiotoxicological point of view, the most important radionuclide is caesium-137. Formed mainly during nuclear explosions, caesium-137 can persist in the soil for many years, from where it constantly enters the food chain. One of the elements of ensuring food safety is the monitoring of its radioactive contamination, mainly with radioactive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The results of regular control tests of animal products conducted in Poland have shown that the most contaminated group of animals are game species, and the most notably contaminated of them is the wild boar ( 13 ). It is well described in the literature that some mushrooms eagerly eaten by animals have a strong propensity to accumulate radioisotopes of caesium ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of regular control tests of animal products conducted in Poland have shown that the most contaminated group of animals are game species, and the most notably contaminated of them is the wild boar ( 13 ). It is well described in the literature that some mushrooms eagerly eaten by animals have a strong propensity to accumulate radioisotopes of caesium ( 7 ).…”
Section: Introductionmentioning
confidence: 99%